STRATEGI IRAN DALAM MERESPONS SANKSI AS PERIODE 2018–2020 - Alir, Adre Anggia; Firnas, Muhamad Adian (Universitas Jenderal Ahmad Yani, 2024)
This research analyzes Iran's strategies in dealing with disruptions in the oil sector due to US sanctions during the 2018–2020 period, coinciding with the US withdrawal from the Joint Comprehensive Plan of Action (JCPOA). Iran initiated its nuclear program in 1957 under Atoms for Peace but suspended it in 1979 under Ayatollah Khomeini. In 2013, Iran engaged in negotiations with the P5+1, leading to the JCPOA three years later. However, in 2018, Trump withdrew the US from the JCPOA, imposing economic sanctions on Iran through five Executive Orders (EO) during 2018-2020, causing disruptions in the oil sector and negatively impacting the country's economy. Iran responded by strengthening bilateral ties and employing innovative approaches. The research, using qualitative and descriptive methods with secondary data sources, such as literature from books, documents, journals, newspapers, magazines, and online articles. The conceptual framework involves international economic sanctions and economic security, revealing that the US sanctions achieved constraining and signaling objectives but failed to coerce Iran. Despite economic challenges, Iran maintained its nuclear program, achieving constraining and signaling goals, while diversifying exports and adopting innovative strategies to counter the sanctions.